Progress in Flight Physics 2013
DOI: 10.1051/eucass/201305069
|View full text |Cite
|
Sign up to set email alerts
|

Experiments on relative receptivity of three-dimensional supersonic boundary layer to controlled disturbances and its development

Abstract: Results of the controlled disturbance experiments in the supersonic boundary layer on a swept wing are considered. The high-frequency glow discharge technique is used for the disturbance generation. The linear development of wave trains is tested in smooth and rough surface conditions of the models. The relative receptivity of a three-dimensional (3D) boundary layer to stationary and nonstationary disturbances is estimated. Obtained that by using microroughness elements located in a swept wing boundary layer, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…It has been also shown that the location of labels relative to the disturbance source aperture has di¨erent in §uence to the mean §ow characteristics and to the initial controlled disturbance amplitude. An additional mean §ow distortion was found [29], if the aperture was in the sticker wake. This e¨ect certainly requires further investigation, as it may limit the development of future transition §ow control technologies at supersonic speeds.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…It has been also shown that the location of labels relative to the disturbance source aperture has di¨erent in §uence to the mean §ow characteristics and to the initial controlled disturbance amplitude. An additional mean §ow distortion was found [29], if the aperture was in the sticker wake. This e¨ect certainly requires further investigation, as it may limit the development of future transition §ow control technologies at supersonic speeds.…”
Section: Introductionmentioning
confidence: 91%
“…The aperture coordinates on the plate are x = 37 ± 0.25 mm and z = 0 (here, x is the distance from the leading edge and z = 0 corresponds to the centerline of the model symmetry). Swept wing model was plane-convex pro¦le and contained a disturbance source aperture of 0.41 mm in diameter [29]. The aperture coordinates on the working surface of the swept wing are x = 57.7 ± 0.25 mm and z = 0.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible to obtain data on the amplitude of total temperature and mass flux pulsations by measurements at different values of the probe overheating. In application of laminar-turbulent transition studies the most progress was achieved in works [15,16]. The decomposition of the pulsations of the supersonic boundary layer on the mass flow and total temperature fluctuation was provided with the help of a constant-temperature hot-wire anemometer with the possibility of automatic scanning by probe overheating.…”
Section: Introductionmentioning
confidence: 99%